2016
DOI: 10.1007/s10964-016-0426-1
|View full text |Cite
|
Sign up to set email alerts
|

Cultural Socialization Across Contexts: Family–Peer Congruence and Adolescent Well-Being

Abstract: Racial/ethnic minority youth live at the intersection of diverse cultures, yet little is known about cultural socialization outside families or how cultural socialization in multiple settings conjointly influences adolescent well-being. In a sample of 236 8th graders (51% female; 89% Latinos, 11% African Americans), we examined adolescents’ perceptions of family and peer cultural socialization toward the heritage culture and the mainstream American culture. A variable-centered approach demonstrated that the so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
67
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 54 publications
(73 citation statements)
references
References 70 publications
5
67
1
Order By: Relevance
“…In previous research, cultural minority youth identified more strongly with their heritage culture when interacting with same-heritage peers as opposed to differentheritage peers (Kiang and Fuligni 2009). However, cultural socialisation practices by peers and their associations with cultural identity remain understudied (Wang and Benner 2016). Therefore, we individually assessed peer cultural socialisation by a same-heritage friend and a different-heritage friend to account for differences in how their socialisation would relate to cultural identity.…”
Section: Cultural Identity and Cultural Socialisationmentioning
confidence: 96%
See 3 more Smart Citations
“…In previous research, cultural minority youth identified more strongly with their heritage culture when interacting with same-heritage peers as opposed to differentheritage peers (Kiang and Fuligni 2009). However, cultural socialisation practices by peers and their associations with cultural identity remain understudied (Wang and Benner 2016). Therefore, we individually assessed peer cultural socialisation by a same-heritage friend and a different-heritage friend to account for differences in how their socialisation would relate to cultural identity.…”
Section: Cultural Identity and Cultural Socialisationmentioning
confidence: 96%
“…Recently, the term cultural socialisation has been defined more broadly to include the preservation and transmission of heritage as well as mainstream culture content (Juang et al 2016;Wang, Benner, and Kim 2015). In this study, we investigate two separate dimensions of peer cultural socialisation, namely peer heritage socialisation and peer mainstream socialisation (Wang and Benner 2016), and their unique associations with heritage and mainstream identity.…”
Section: Cultural Identity and Cultural Socialisationmentioning
confidence: 99%
See 2 more Smart Citations
“…The present study focuses on intragroup contact across everyday situations as an important process that promotes adolescents' positive feelings toward their ethnic/racial groups (Yip et al., ). A nascent body of work suggests that adolescents receive messages about what it means to be a member of their ethnic/racial group from various socialization agents in and outside their families (Hughes, McGill, Ford, & Tubbs, ; Wang & Benner, ), and this process is particularly salient in their interactions with same‐ethnic others (Kiang & Fuligni, ). Indeed, empirical work demonstrates that adolescents with greater intragroup contact are more likely to report an achieved ERI (Phinney, Romero, Nava, & Huang, ) or changes in their ERI status (Yip, Seaton, & Sellers, ).…”
Section: Parental Cultural Socialization and Ethnic/racial Private Rementioning
confidence: 99%